2020
DOI: 10.1002/anie.201916316
|View full text |Cite
|
Sign up to set email alerts
|

The Glutathione/Metallothionein System Challenges the Design of Efficient O2‐Activating Copper Complexes

Abstract: Copper complexes are of medicinal and biological interest, including as anticancer drugs designed to cleave intracellular biomolecules by O 2 activation. To exhibit such activity,the copper complex must be redox active and resistant to dissociation. Metallothioneins (MTs) and glutathione (GSH) are abundant in the cytosol and nucleus.Because they are thiol-richr educing molecules with high Cu I affinity,t hey are potential competitors for ac opper ion bound in ac opper drug. Herein, we report the investigation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(48 citation statements)
references
References 40 publications
3
44
0
1
Order By: Relevance
“…This can be explained by the formation of a mixed-ligand complex with GSH via the coordination of the thiolate at the fourth coordination site of the copper(II), as also reported for similar complexes. 6 , 42 , 43 For Cu-COTI-2, this was also proven by mass spectrometry measurements, clearly indicating the respective GSH-Cu-COTI-2 complex at m/z = 735 ( Figure S6 ). This GSH-adduct formation was similar for all copper(II) complexes, but over time, a very different behavior was observed.…”
Section: Resultssupporting
confidence: 59%
“…This can be explained by the formation of a mixed-ligand complex with GSH via the coordination of the thiolate at the fourth coordination site of the copper(II), as also reported for similar complexes. 6 , 42 , 43 For Cu-COTI-2, this was also proven by mass spectrometry measurements, clearly indicating the respective GSH-Cu-COTI-2 complex at m/z = 735 ( Figure S6 ). This GSH-adduct formation was similar for all copper(II) complexes, but over time, a very different behavior was observed.…”
Section: Resultssupporting
confidence: 59%
“…Recently, Santoro et al. have reported that Cu I and Cu II oxidation states of Cu-catalysts during O 2 activation under ascorbate are unstable against GSH/MT system ( Santoro et al., 2020 ). Therefore, intercellular Cu-trafficking proteins are a challenge for the design of Cu-ATCUN complexes as oxidative cleavage catalysts in cells.…”
Section: Conclusion and Future Challengesmentioning
confidence: 99%
“…Although the production of ROS by redox reactions has been recently challenged [ 78 ], the generation of ROS via thiol-mediated reduction of copper(II) to copper(I) has been assumed as the major mechanism of anticancer activity of many copper(II) TSC complexes [ 62 ]. The presence of reducing agents such as biologically relevant GSH is crucial for the redox reactivity of copper(II) TSC complexes [ 62 ].…”
Section: Resultsmentioning
confidence: 99%